Biography of the Mufti Sultanate in West Kalimantan: H. Muhammad Basiuni Imran (1885-1976 AD) and H. Ismail Mundu (1870-1957 AD) - Ihsan Nurmansyah,; Sherli Kurnia Oktaviana, (Journal of Islamic History and Manuscript, 2022)
H. Muhammad Basiuni Imran and H. Ismail Mundu are mufti or charismatic clerics who are popular now in the West Kalimantan area. Both lived contemporaneously, and their work in various scientific, social, and political fields has brought them to a level of popularity that is not only in the Malay Archipelago world but also in the Islamic world. Therefore, it is essential to study their biographies, starting with their family background, education, academic career, environment, and work. The method used is the historical method and comparative research. The results of this study are as follows 1) both mufti comes from religious family backgrounds, as seen from the childhood of H. Muhammad Basiuni Imran studied religion from his father, H. Muhammad Imran, while H. Ismail Mundu studied theology with his uncle, H. Muhammad bin H. Ali; 2) the two mufti used the Middle East as their intellectual space. It was seen that H. Muhammad Basiuni Imran performed the hajj and studied simultaneously in Mecca and Egypt, while H. Ismail Mundu performed the hajj three times and only studied in Mecca; 3) both multitasked with explaining to the public religious issues when H. Muhammad Basiuni Imran, as mufti in the Sultanate of Sambas, wrote Tafsir Tujuh Surah and Ayat as-Siyam as a response to the problems faced by the Malay community. Meanwhile, H. Ismail Mundu held the position of mufti in the Kubu Sultanate, writing Bugis translation of the holy book of the Qur’an as a response problem faced by the Bugis people.